Research in Health Care / Concepts, Designs and Methods - Nelson Thornes; Sim Julius; Wright Chris (2000)
A comprehensive book that covers the essential stages in research, from posing the right questions, designing your study, through to the methods for collecting, presenting and analyzing you data. Acknowledgements, Fundamentals, Introduction, Basic Concepts and Principles, Formulating Ideas for Research, Designing and Executing a Study, Basic Elements of Research Design, Designing an Exploratory Study, Designing a Descriptive Study, Designing an Explanatory Study, Sampling, Validity and Reliability and Allied Concepts, Presenting and Analyzing Data, Recording and Organizing Data from Explanatory Studies, Analyzing Data from Exploratory Studies, Presenting Data from Exploratory Studies, Presenting Data from Descriptive and Exploratory Studies, Analyzing Data from Descriptive and Exploratory Studies: Principles, Analyzing Data from Descriptive and Exploratory Studies: Procedures, More Specialized Issues, Single Instance Research, Systematic Review and Meta - Analysis and Measures of Treatment Effect, Analyzing Data from Descriptive and Explanatory Studies: Further Principles and Procedures, References, Appendices, Case Studies, Analysis of Variance: Models, Index.